2016
DOI: 10.4103/1658-354x.179096
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of epidural local anesthetic and dexamethasone in providing postoperative analgesia: A meta-analysis

Abstract: Background:Dexamethasone is a potent anti-inflammatory, analgesic, and antiemetic drug. Individual randomized controlled trials found a possible benefit of epidural dexamethasone. The purpose of this meta-analysis is to estimate the benefit of epidural dexamethasone on postoperative pain and opioid consumption and to formulate a recommendation for evidence-based practice.Materials and Methods:Prospective, randomized controlled trials comparing the analgesic efficacy of epidural local anesthetic and dexamethaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Epidural dexamethasone in dose range of 4-8 mg has also been investigated for its analgesic efficacy and a recent meta-analysis has looked at its effectiveness[ 151 ]. The meta-analysis showed the advantages of the use of dexamethasone as an adjuvant to epidural local anaesthetics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epidural dexamethasone in dose range of 4-8 mg has also been investigated for its analgesic efficacy and a recent meta-analysis has looked at its effectiveness[ 151 ]. The meta-analysis showed the advantages of the use of dexamethasone as an adjuvant to epidural local anaesthetics.…”
Section: Discussionmentioning
confidence: 99%
“…The meta-analysis showed the advantages of the use of dexamethasone as an adjuvant to epidural local anaesthetics. However, it also highlighted the need of further well powered studies to establish its safety in terms of neurological complications[ 151 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were obtained in humans with preoperative administration of dexamethasone (8 mg) given by epidural route providing analgesic effects in patients undergoing abdominal hysterectomy 11 . Patients who received epidural dexamethasone either alone or combined with bupivacaine had a longer duration of postoperative analgesia and less analgesic consumption compared to a control group that received IV dexamethasone and epidural bupivacaine 17 .…”
Section: ■ Discussionmentioning
confidence: 99%
“…In humans, lumbar epidural dexamethasone has been used to treat patients with postoperative pain resulting from lower abdominal surgeries 10,17 , hysterectomy 11 or orchiopexy and back pain 1,18,19 . The authors are unaware of any studies on the use of epidural dexamethasone in dogs to relieve pain and increase the duration of action of the lignocaine local anaesthetic in the postoperative period.…”
mentioning
confidence: 99%
“…The half-life of dexamethasone is between 36 and 54 h, and its effects are most apparent in the first 48 h [ 1 ]. Dexamethasone as an adjuvant to epidural local anesthetics has been studied [ 12 ]. To date, no trial has reported neurotoxicity attributable to dexamethasone dosage.…”
Section: Discussionmentioning
confidence: 99%